Infused Water Mentimun Untuk Menurunkan Hipertensi - Yuliza, Emi; Solehudin, Solehudin (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Hypertension is a major risk factor for cardiovascular disease, such as heart attack and stroke. Cucumbers contain lots of water and electrolytes which can help maintain blood pressure within normal limits. This article aims to explore cucumber, which is a simple drink that can contribute to efforts to lower blood pressure. Community service activities in the form of health education involve nursing professional students along with community nursing clinical practice activities. The results obtained showed that after being given counseling, the level of public knowledge about hypertension and its treatment using cucumber juice increased by 49.5%. Meanwhile, the average blood pressure decreased by 20 mmHg after using cucumber juice for 1 week. The combination of infused water with cucumber has potential health benefits, especially in the context of lowering blood pressure. Cucumbers contain potassium, have a mild diuretic effect, and can support body hydration, all of which can contribute to blood pressure management.